2020
DOI: 10.3892/ijmm.2020.4603
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑383‑5p inhibits the proliferation and promotes the apoptosis of gastric cancer cells by targeting cancerous inhibitor of PP2A

Abstract: The aberrant expression of microRNA (miRNAor miR)-383-5p has been found in numerous types of cancer. However, the function of miR-383-5p in gastric cancer (Gc) remains elusive and requires further investigation. In the present study, the level of miR-383-5p and cancerous inhibitor of PP2A (cIP2A) in Gc cell lines was determined by reverse transcription-quantitative PcR analysis. Gc cell proliferation, apoptosis and cell cycle distribution were determined by the MTT assay and flow cytometry, respectively. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…CIP2A inactivates protein phosphatase 2A (PP2A), which reduces the phosphorylation of Akt (protein kinase B) and stabilizes the c-Myc proto-oncogene in tumor cells ( Soofiyani et al, 2017a ). In the miR-383-5p/CIP2A pathway, decreased miR-383-5p expression together with higher CIP2A expression was found in GC cells compared with normal gastric epithelial cells ( Li et al, 2020a ). CIP2A promotes cancer cell proliferation and prevents apoptosis ( Soofiyani et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…CIP2A inactivates protein phosphatase 2A (PP2A), which reduces the phosphorylation of Akt (protein kinase B) and stabilizes the c-Myc proto-oncogene in tumor cells ( Soofiyani et al, 2017a ). In the miR-383-5p/CIP2A pathway, decreased miR-383-5p expression together with higher CIP2A expression was found in GC cells compared with normal gastric epithelial cells ( Li et al, 2020a ). CIP2A promotes cancer cell proliferation and prevents apoptosis ( Soofiyani et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the mechanism of miRNA regulating the targeted genes, the predicted miRNA should be down-regulated and negatively correlated with MTHFD2 expression in bladder cancer and miR-383-5p met the two required conditions. Previous studies also showed that miR-383-5p suppressed the proliferation and induced the apoptosis in gastric cancer cells [30]. Hence, miR-383-5p was assumed to be the most potential upstream miRNA of MTHFD2.…”
Section: Discussionmentioning
confidence: 90%
“…According to the mechanism of miRNA regulating the targeted genes, the predicted miRNA should be down-regulated and negatively correlated with MTHFD2 expression in bladder cancer and miR-383-5p met the two required conditions. Previous studies also showed that miR-383-5p suppressed the proliferation and induced the apoptosis in gastric cancer cells [40]. Hence, miR-383-5p was assumed to be the most potential upstream miRNA of MTHFD2.…”
Section: Discussionmentioning
confidence: 90%